Landscape fragmentation assessment in the Garzón coastal lagoon, Uruguay (INNOTEC, 2022)
This investigation characterized and quantified the effects of land uses and anthropic activities on a landscape configuration over a period of 15 years from 2000 thru 2015 within the catchment area of Laguna Garzón in Uruguay. For this end, four official data layers of land uses based on remote sensing techniques were used based on a Geographic Information System approach. In addition, landscape metrics were computed in order to evaluate the landscape fragmentation process. The results showed that in the last 15 years those anthropic classes, including afforestation and cultivated areas, experienced surface size growth, while natural areas experienced a reduction. Furthermore, a high quantity of changes from anthropic activities took place in the southern region of the watershed, particularly cultivated areas that have been concentrated there since 2008. Landscape metrics revealed that the landscape within the protected area of Laguna Garzón experienced habitat fragmentation during the 15 years period.
Keywords: land use; landscape configuration; GIS analysis; protected areas